Napier Grass Pyrolysis: Kinetic and Thermodynamics Analysis - Manatura, Kanit (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
The pyrolysis behavior, kinetics and thermodynamics analysis of Napier grass were studied. A thermogravimetric analyzer (TGA) and differential thermal analyzer (DTA), at four heating rates: 5, 10, 20 and 30 oC/min were used in the experiments. Pyrolysis parameters were determined using model-fitting with the Coat-Redfern method. The results showed that the grass was roughly decomposed into moisture removal and volatiles release zones. The approximate peak temperature occurred in the major stage during 298 to 337 oC. The characteristic temperatures moved to a higher temperature during thermal degradation. The apparent activation energy and pre-exponential factor also increased with increasing heating rate. The positive values of enthalpies (ΔH), Gibbs free energies (ΔG) and the negative value of entropies (ΔS) exhibited that the Napier grass was endothermic but some exothermic reactions were also found, due to the presence of oxygen in its original components.